Development of Computer-Assisted Learning Media Material on the Relationship Between Coefficients and Discriminants of Quadratic Functions - Widuri, Nabila Ekaputri; Rahardi, Rustanto; Nusantara, Toto; Nasution, Syaiful Hamzah (PRISMA, 2025)
This study aims to create media products that are suitable for use and make it easier for students to understand the material concept of the relationship between coefficients and discriminants of quadratic functions with their graphs. The media was developed using GeoGebra and student worksheets. This study uses the development of the ADDIE model with the stages of analysis, design, development, implementation, evaluation. The developed media was tested on 29 students of SMP Salahuddin class IX D. The developed media was declared valid based on the validator's assessment with the percentage of validity of interview guidelines 97%, learning media 92%, student worksheets 94%, lesson plans 94%, quizzes 91%, 95% student response questionnaire, 93% student activity observation sheet, 92% teacher activity observation sheet. The media is declared practical based on the teacher's assessment with the percentage of practicality of student response questionnaires 88%, student activity observation sheets 96%, teacher activity observation sheets 96%. The media was also declared effective based on student quiz assessments with a percentage of 93% of students getting an average score of at least 80 completeness requirements the graph.